Battery monomer, preparation method of battery monomer and power utilization device

The preparation of positive electrode active materials by one-step liquid phase co-deposition method, controlling the molar ratio of lithium element to iron element and adding carbon source, etc., solve the problems of complex and high cost of preparation of lithium iron phosphate materials, and achieve high cycle stability and gram capacity of battery cells.

CN119852395AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411615870.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-04-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing lithium iron phosphate materials are complex in the process of preparation, costly, and difficult to take into account both cycle stability and capacity.

Method used

A positive electrode active material was prepared by one-step liquid phase co-deposition method, and the molar ratio of lithium element to iron element was controlled to be less than or equal to 1.06 with a molar ratio of more than 1, reducing the iron dissolution rate, and improving the conductivity and gram capacity by adding carbon sources and additives.

Benefits of technology

Excellent cycle stability and good gram capacity of the battery cell are achieved, while reducing the production cost of lithium iron phosphate material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852395A_ABST
    Figure CN119852395A_ABST
Patent Text Reader

Abstract

The invention provides a battery monomer, a preparation method of the battery monomer and a power utilization device. The battery monomer comprises a positive pole piece, a negative pole piece and an electrolyte, the positive pole piece comprises a positive current collector and a positive film layer arranged on at least one side of the positive current collector, the positive film layer comprises a positive active material, the positive active material comprises a lithium-containing phosphate material, the iron dissolution rate of the positive active material is 0-10mg / L, and the lithium-containing phosphate material is a lithium-containing phosphate material. And the molar ratio of the lithium element to the iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06. The battery monomer provided by the invention has good cycling stability and good gram volume. According to the preparation method of the positive electrode active material, the preparation process of the positive electrode active material is simplified, the production cost is reduced, and meanwhile, the iron dissolution rate of the positive electrode active material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a battery cell, a method for preparing the battery cell, and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the popularization of secondary battery applications, higher requirements have been put forward for their cycle performance and service life.

[0003] Lithium iron phosphate materials have advantages such as high safety and play an important role in the application of secondary batteries. However, the process of preparing lithium iron phosphate is complicated and expensive, and the prepared lithium iron phosphate cannot take into account both cycle stability and gram capacity. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems and aims to solve at least one of the technical problems existing in the prior art. To this end, the present application provides a battery cell, a method for preparing the battery cell and an electrical device.

[0005] The first aspect of the present application provides a battery cell, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a lithium-containing phosphate material, the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L, and the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06.

[0006] The iron dissolution rate of the positive electrode active material is within the above range, which reduces the content of iron ions dissolved from the positive electrode active material during the battery charging and discharging process, thereby reducing the risk of iron ions precipitating at the negative electrode to form iron dendrites and dendrites piercing the negative electrode solid electrolyte membrane (SEI membrane), which is beneficial to improving the battery cycle stability. The molar ratio of lithium to iron in the positive electrode active material is within the above range, which is beneficial to improving the gram capacity of the positive electrode active material and the lithium ion diffusion coefficient. In summary, the battery cell of the embodiment of the present application has excellent cycle stability while taking into account good gram capacity.

[0007] In any embodiment, the iron dissolution rate of the positive electrode active material is 0 mg / L-5 mg / L.

[0008] The iron dissolution rate of the positive electrode active material is within the above range, which is beneficial to further improve the cycle stability of the battery.

[0009] In any embodiment, based on the total mass of the positive electrode active material, the mass content of sulfur in the positive electrode active material is 0 ppm-50 ppm.

[0010] The mass content of sulfur element in the positive electrode active material is within the above range, which is beneficial to reduce the content of sulfur impurities dissolved in the electrolyte and reduce the degree of side reactions of sulfur impurities, thereby further improving the cycle stability of the secondary battery of the embodiment of the present application.

[0011] In any embodiment, the Dv90 of the positive electrode active material is 2 μm to 5 μm.

[0012] The Dv90 of the positive electrode active material is within the above range, indicating that the proportion of large-size active material particles in the positive electrode active material is low, which is beneficial to shortening the diffusion distance of lithium ions in the positive electrode active material, thereby improving the lithium ion diffusion coefficient of the positive electrode active material, and is beneficial to improving the battery rate performance.

[0013] In any embodiment, the Dv99 of the positive electrode active material is 4 μm-8 μm.

[0014] The Dv99 of the positive electrode active material is within the above range, indicating that the proportion of large-size active material particles in the positive electrode active material is low, which is beneficial to further shorten the diffusion distance of lithium ions in the positive electrode active material, and then further improve the lithium ion diffusion coefficient of the positive electrode active material, which is beneficial to further improve the battery rate performance.

[0015] In any embodiment, the positive electrode active material has a gram capacity of 145 mAh / g to 152 mAh / g at a discharge rate of 0.33C.

[0016] The gram capacity of the positive electrode active material is within the above range, which is beneficial to improving the energy density of the battery.

[0017] In any embodiment, the lithium ion diffusion coefficient of the positive electrode active material is 3×10 -14 cm 2 / s-8×10 - 14 cm 2 / s.

[0018] When the lithium ion diffusion coefficient of the positive electrode active material is within the above range, it is beneficial to further improve the rate performance of the battery.

[0019] In any embodiment, the lithium-containing phosphate includes a component having the following general formula:

[0020] Li m Fe x P y O j Qq ,

[0021] Among them, Q includes one or more of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.8≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0≤q≤0.1.

[0022] In any embodiment, the molar ratio of lithium to iron in the positive electrode active material is 1.01-1.06; and / or

[0023] The molar ratio of the iron element to the phosphorus element in the positive electrode active material is 0.96-1, and optionally, 0.96-0.98.

[0024] The molar ratio of lithium to iron and the molar ratio of iron to phosphorus in the positive electrode active material are within the above ranges, which is conducive to further reducing the impurities in the positive electrode active material, further reducing the iron dissolution rate of the positive electrode active material, and further improving the gram capacity and cycle stability of the positive electrode active material. Furthermore, the appropriate molar ratio of lithium to iron and the molar ratio of iron to phosphorus are also conducive to further improving the lithium ion diffusion coefficient of the positive electrode active material.

[0025] A second aspect of the present application provides a method for preparing a battery cell, comprising at least the following steps:

[0026] Preparation of positive electrode active material: mixing raw materials including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; treating the slurry to obtain a precursor material; sintering the precursor material to obtain the positive electrode active material, wherein the positive electrode active material includes a lithium-containing phosphate material, the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06, and the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L;

[0027] The battery cell is prepared using the positive electrode active material.

[0028] Compared with the solid phase method for preparing positive electrode active materials, the preparation method of the present application prepares the positive electrode active material by a one-step liquid phase co-precipitation method, which does not require a complicated precursor preparation process and high temperature and high pressure reaction conditions, thereby reducing the production cost of lithium iron phosphate materials.

[0029] The preparation method of the embodiment of the present application controls the molar ratio of lithium to iron in the positive electrode active material within the above range, so that the positive electrode active material has excellent gram capacity, and is conducive to the formation of pure phase lithium iron phosphate during the sintering process of preparing the positive electrode active material, thereby reducing the iron dissolution rate of the positive electrode active material; the iron, phosphorus and lithium elements in the positive electrode active material prepared by the liquid phase co-precipitation method adopted in the embodiment of the present application are evenly distributed at the atomic level, which is conducive to enhancing the binding of phosphate to iron ions, thereby further reducing the iron dissolution rate of the positive electrode active material, so that the iron dissolution rate of the positive electrode active material meets the above range. The secondary battery has excellent cycle stability and good gram capacity.

[0030] In any embodiment, the first lithium source comprises lithium sulfate.

[0031] Lithium sulfate has the advantages of abundant sources, low cost, good water solubility, etc., and is suitable for the preparation method of the embodiment of the present application, which is beneficial to reduce the cost of raw materials, thereby further reducing the production cost of lithium iron phosphate materials.

[0032] In any embodiment, the molar ratio of the lithium element in the first lithium source to the iron element in the iron source is greater than 1 and less than or equal to 1.06. Optionally, the molar ratio of the lithium element in the first lithium source to the iron element in the iron source is 1.01-1.06.

[0033] In any embodiment, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-1. Optionally, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-0.98.

[0034] When the molar ratio of lithium in the first lithium source to iron in the iron source, and the molar ratio of iron in the iron source to phosphorus in the phosphorus source are within the above ranges, it is beneficial to form pure phase lithium iron phosphate during the sintering process, further reduce the iron dissolution rate of the prepared positive electrode active material, and further improve the gram capacity and cycle stability of the positive electrode active material. Furthermore, the appropriate molar ratio of lithium to iron, and the molar ratio of iron to phosphorus are also beneficial to further improve the lithium ion diffusion coefficient of the positive electrode active material.

[0035] In any embodiment, the preparation of the positive electrode active material comprises at least the following steps:

[0036] The raw materials including the first lithium source, the iron source and the phosphorus source are mixed with the solvent to obtain the slurry; a pH adjuster is added to the slurry until the pH value is greater than or equal to 7 to obtain a second slurry; the second slurry is separated to obtain the precursor material; and the precursor material is sintered to obtain the positive electrode active material.

[0037] By adding a pH adjuster to adjust the pH of the slurry to be greater than or equal to 7, it is beneficial to further precipitate the lithium ions in the slurry, so that the molar ratio of lithium element to iron element in the precursor material is within a suitable range, for example, the molar ratio is 1.01-1.06, which is beneficial to the formation of a purer lithium iron phosphate during the sintering process, so that the iron dissolution rate of the prepared positive electrode active material is within a suitable range, further taking into account the excellent gram capacity and cycle stability.

[0038] In any embodiment, the pH adjuster includes one or more of ammonium carbonate and ammonium bicarbonate.

[0039] The above-mentioned types of pH adjusters are compatible with the preparation method of the present application.

[0040] In any embodiment, the preparation of the positive electrode active material further includes: separating the second slurry to obtain a solid material; adding a carbon source to the solid material and grinding it to obtain the precursor material; and sintering the precursor material to obtain the positive electrode active material.

[0041] The precursor material includes a carbon source. The surface of the positive electrode active material prepared by sintering is evenly coated with a highly conductive carbon layer, which is beneficial to improving the conductivity of the positive electrode active material. In addition, carbon can be used as a reducing agent to reduce Fe 3+ Reduction to Fe 2+ , which is conducive to further improving the gram capacity of the positive electrode active material.

[0042] In any embodiment, the mass content of the carbon source is 1%-5% based on the mass of the solid material.

[0043] By controlling the amount of carbon source added within a suitable range, the thickness of the carbon coating layer on the surface of the prepared positive electrode active material is suitable, which is beneficial to further improve the conductivity and gram capacity of the positive electrode active material.

[0044] In any embodiment, the preparation of the positive electrode active material includes at least the following steps: mixing the raw materials including the first lithium source, the iron source, and the phosphorus source with the solvent to obtain the slurry; separating the slurry to obtain a first solid material; washing the first solid material, and sintering the first solid material after washing to obtain a second solid material; adding a second lithium source to the second solid material, and grinding to obtain the precursor material; sintering the precursor material to obtain the positive electrode active material.

[0045] The preparation method of the present application obtains the first solid material after washing, precipitation and separation, which can effectively remove the impurity ions such as sulfate introduced by the first lithium source in the first solid material, reduce the impurity content dissolved into the electrolyte, and then reduce the degree of side reactions, and further improve the cycle performance of the secondary battery. However, washing will dissolve the lithium element in the first solid material, resulting in a molar ratio of lithium element to iron element in the second solid material that is too small. If it is directly used for sintering to prepare positive electrode active materials, it will increase the iron dissolution rate of the positive electrode active material, for example, greater than 10 mg / L, and reduce its gram capacity; therefore, further, the preparation method of the present application adds a second lithium source to the second solid material, so that the molar ratio of lithium element to iron element in the precursor material used for sintering to prepare positive electrode active materials is within a suitable range, which is conducive to the formation of a more pure phase of lithium iron phosphate during the sintering process, so that the iron dissolution rate of the positive electrode active material is within a suitable range, and the prepared positive electrode active material has good cycle stability and excellent gram capacity. In summary, the above preparation method reduces the production cost of lithium iron phosphate. At the same time, the obtained positive electrode active material has a lower iron dissolution rate and a further reduced impurity ion content, which is beneficial to further improve the cycle performance of the positive electrode active material of the present application while taking into account the gram capacity.

[0046] In any embodiment, based on the total mass of the positive electrode active material, the mass content of sulfur in the positive electrode active material is 0 ppm-50 ppm.

[0047] When lithium sulfate is used as the first lithium source, the first solid material obtained after washing, precipitation and separation can effectively remove sulfate ions in the first solid, so that the mass content of sulfur element in the positive electrode active material is within the above range, which is beneficial to further improve the cycle performance of the positive electrode active material of the present application.

[0048] In any embodiment, the first solid material is washed 3-5 times.

[0049] Controlling the number of washing times within the above range is beneficial to dissolving as little lithium as possible in the first solid material while removing impurities to the greatest extent, which is beneficial to further reduce the cost of subsequent lithium replenishment and take into account the gram capacity and cycle stability of the secondary battery.

[0050] In any embodiment, the second lithium source includes one or more of lithium carbonate and lithium hydroxide.

[0051] In any embodiment, the temperature for sintering the first solid material is 300° C.-400° C.; and / or

[0052] The time for sintering the first solid material is 3h-5h.

[0053] Controlling the temperature and time of sintering the first solid material within the above range is conducive to removing moisture from the first solid material and converting it into a second solid material including an iron phosphate phase. By testing the iron-lithium ratio of the second solid material, it is convenient to calculate the amount of the second lithium source that needs to be added. The above sintering temperature and time are conducive to uniformly mixing the sintered second solid material and the second lithium source to obtain a precursor material, thereby improving the efficiency of subsequent sintering of the precursor material.

[0054] In any embodiment, the preparation of the positive electrode active material further comprises: adding the second lithium source and the carbon source to the second solid material, and grinding to obtain the precursor material; and sintering the precursor material to obtain the positive electrode active material.

[0055] The precursor material includes a carbon source. The surface of the positive electrode active material prepared by sintering is evenly coated with a highly conductive carbon layer, which is beneficial to improving the conductivity of the positive electrode active material. In addition, carbon can be used as a reducing agent to reduce Fe 3+ Reduction to Fe 2+ , which is conducive to further improving the gram capacity of the positive electrode active material.

[0056] In any embodiment, the mass content of the carbon source is 1%-5% based on the mass of the second solid material.

[0057] By controlling the amount of carbon source added within a suitable range, the thickness of the carbon coating layer on the surface of the prepared positive electrode active material is suitable, which is beneficial to further improve the conductivity and gram capacity of the positive electrode active material.

[0058] In any embodiment, the temperature of sintering the precursor material is 650° C.-750° C.; and / or

[0059] The time for sintering the precursor material is 5h-15h.

[0060] Controlling the temperature and time of sintering the precursor within the above range is beneficial to improving the conversion rate of the precursor material into the lithium iron phosphate phase, further reducing the iron dissolution rate of the positive electrode active material and improving the gram capacity of the positive electrode active material; further, the above sintering temperature and time are beneficial to the reaction of the added carbon source and trivalent iron ions into divalent iron ions, and the surface of the sintered positive electrode active material has a uniform carbon coating layer, thereby further improving the gram capacity and cycle stability of the positive electrode active material.

[0061] In any embodiment, the iron source comprises one or more of ferrous sulfate, ferric sulfate; and / or

[0062] The phosphorus source includes one or more of diammonium phosphate, phosphoric acid, and diammonium hydrogen phosphate.

[0063] A third aspect of the present application provides an electrical device, which includes the battery cell of the first aspect of the present application or the battery cell prepared according to the preparation method of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 is a scanning electron microscope image of a positive electrode active material prepared in one embodiment of the present application;

[0065] Figure 2 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0066] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown;

[0067] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application;

[0068] Figure 5 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0069] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0070] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0071] Description of reference numerals:

[0072] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0073] Hereinafter, the battery cell, the method for preparing the battery cell, and the implementation mode of the electric device of the present application will be specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0074] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0075] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0076] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0077] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0078] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0079] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0080] Lithium iron phosphate has advantages such as high safety and is a research hotspot in the field of secondary battery positive electrode active materials. However, the preparation process of lithium iron phosphate materials is complex and the production cost is high, and the prepared lithium iron phosphate materials often have poor cycle performance or low gram capacity. Therefore, taking into account the cycle performance and gram capacity of lithium iron phosphate materials and / or reducing the preparation cost of lithium iron phosphate materials are urgent problems to be solved in the field of positive electrode active materials.

[0081] [Battery Cell]

[0082] Based on this, the present application provides a battery cell, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a lithium-containing phosphate material, the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L, and the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06.

[0083] In some embodiments, the iron dissolution rate is the iron dissolution rate of the positive electrode active material in an initial state or the iron dissolution rate of the positive electrode active material obtained by disassembling a working battery.

[0084] In this article, the iron dissolution rate of the positive electrode active material can be measured by methods and equipment known in the art. The example is as follows: disassemble the battery to take out the positive electrode plate, peel off the active material film layer of the positive electrode plate, dissolve and filter with N-methylpyrrolidone (NMP) solvent, wash with NMP to remove the binder; dry and obtain powder for subsequent characterization tests. Weigh a certain mass of 5g of powder, add 100mL of 0.008mol / L hydrochloric acid to obtain a dispersed solution, the concentration of the positive electrode active material in the dispersed solution is 0.05g / mL, stir at 25°C for 30min, then stand in a 25°C water bath for 2h, filter to obtain a filtrate, and test the concentration of iron ions in the filtrate, for example, use inductive plasma emission spectroscopy (ICP) to test the iron ion concentration in the filtrate, and the test method refers to the national standard EPA 6010D-2018 and JY / T 0567-2020.

[0085] In some embodiments, the iron dissolution rate of the positive electrode active material can be 0 mg / L, 3 mg / L, 5 mg / L, 6 mg / L, 8 mg / L, 10 mg / L, or a range consisting of any two of the above iron dissolution rates or other unlisted values ​​within the range.

[0086] In this article, the molar ratio of lithium to iron in the positive electrode active material can be measured by methods and equipment known in the art. The following example is to peel off the active material film layer of the positive electrode plate, dissolve and filter it with NMP solvent, wash it thoroughly with NMP to remove the binder; dry it to obtain a powder for subsequent characterization testing. Weigh a certain mass (for example, 0.5g) of powder, add a certain volume (for example, 10mL) of aqua regia microwave digestion for a certain time (for example, 20min), then measure a certain volume (for example, 1mL) of sample and dilute it to a suitable volume (for example, 100mL) for standby use. The content of Li and Fe elements in the above samples was tested according to the national standard EPA6010D-2018JY / T 0567-2020 inductively coupled plasma emission spectrometry, and the molar ratio of Li / Fe in the positive electrode active material was calculated.

[0087] In some embodiments, the molar ratio of lithium to iron in the positive electrode active material may be 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, or any range of any two of the above molar ratios or other values ​​not listed within the range.

[0088] The iron dissolution rate of the positive electrode active material is within the above range, which reduces the content of iron ions dissolved from the positive electrode active material during the battery charging and discharging process, thereby reducing the risk of iron ions precipitating at the negative electrode to form iron dendrites and dendrites piercing the negative electrode solid electrolyte membrane (SEI membrane), which is beneficial to improving the battery cycle stability. The molar ratio of lithium to iron in the positive electrode active material is within the above range, which is beneficial to improving the gram capacity of the positive electrode active material and the lithium ion diffusion coefficient. In summary, the battery cell of the embodiment of the present application has excellent cycle stability while taking into account good gram capacity.

[0089] In some embodiments, the iron dissolution rate of the positive electrode active material is 0 mg / L-5 mg / L.

[0090] The iron dissolution rate of the positive electrode active material is within the above range, which is beneficial to further improve the cycle stability of the battery.

[0091] In some embodiments, the mass content of sulfur in the positive electrode active material is 0 ppm-50 ppm based on the total mass of the positive electrode active material.

[0092] In some embodiments, based on the total mass of the positive electrode active material, the mass content of sulfur in the positive electrode active material can be 0ppm, 5ppm, 10ppm, 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, or a range consisting of the mass contents of any two of the above sulfur elements or other unlisted values ​​within the range.

[0093] In this article, based on the total mass of the positive electrode active material, the mass content of sulfur in the positive electrode active material can be measured by methods and equipment known in the art. The example is as follows: disassemble the battery to take out the positive electrode plate, peel off the active material film layer of the positive electrode plate, dissolve and filter it with NMP solvent, wash it thoroughly with NMP to remove the binder; dry it to obtain a powder for subsequent characterization testing. Weigh a certain mass (for example, 0.5g) of powder, add a certain volume (for example, 10mL) of aqua regia microwave digestion for a certain time (for example, 20min), then measure a certain volume (for example, 1mL) of sample and dilute it to a suitable volume (for example, 100mL) for standby use. The sulfur content in the above samples was tested by inductively coupled plasma emission spectrometry according to the national standard EPA 6010D-2018JY / T 0567-2020, and the mass content of sulfur in the positive electrode active material was finally calculated.

[0094] The mass content of sulfur element in the positive electrode active material is within the above range, which is beneficial to reduce the content of sulfur impurities dissolved in the electrolyte and reduce the degree of side reactions of sulfur impurities, thereby further improving the cycle stability of the secondary battery of the embodiment of the present application.

[0095] In some embodiments, the Dv90 of the positive electrode active material is 2 μm-5 μm.

[0096] As used herein, the term "Dv90" refers to the particle size at which the volume cumulative particle size distribution percentage in the particles reaches 90%.

[0097] In some embodiments, the Dv90 of the positive electrode active material may be 2 μm, 3 μm, 4 μm, 5 μm, or a range consisting of any two of the above Dv90 values ​​or other values ​​not listed within the range.

[0098] In this article, the Dv90 of the positive electrode active material can be measured by methods and equipment known in the art. For example, take an appropriate amount of the positive electrode active material to be tested, refer to GB / T19077-2016, and use a laser particle size analyzer for measurement. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0099] The Dv90 of the positive electrode active material is within the above range, indicating that the proportion of large-size active material particles in the positive electrode active material is low, which is beneficial to shortening the diffusion distance of lithium ions in the positive electrode active material, thereby improving the lithium ion diffusion coefficient of the positive electrode active material, and is beneficial to improving the battery rate performance.

[0100] In some embodiments, the positive electrode active material has a Dv99 of 4 μm to 8 μm.

[0101] As used herein, the term "Dv99" refers to the particle size corresponding to the 99% cumulative particle size distribution percentage in the particles.

[0102] In some embodiments, the Dv99 of the positive electrode active material may be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or a range consisting of any two of the above Dv99 values ​​or other values ​​not listed within the range.

[0103] In this article, the Dv99 of the positive electrode active material can be measured by methods and equipment known in the art. For example, take an appropriate amount of the positive electrode active material to be tested, refer to GB / T19077-2016, and use a laser particle size analyzer for determination. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0104] The Dv99 of the positive electrode active material is within the above range, indicating that the proportion of large-size active material particles in the positive electrode active material is low, which is beneficial to further shorten the diffusion distance of lithium ions in the positive electrode active material, and then further improve the lithium ion diffusion coefficient of the positive electrode active material, which is beneficial to further improve the battery rate performance.

[0105] In some embodiments, the gram capacity of the positive electrode active material at a discharge rate of 0.33C is 145 mAh / g to 152 mAh / g.

[0106] In some embodiments, the gram capacity of the positive electrode active material at a discharge rate of 0.33C can be 145mAh / g, 146mAh / g, 147mAh / g, 148mAh / g, 149mAh / g, 150mAh / g, 151mAh / g, 152mAh / g, or a range consisting of any two of the above gram capacities or other unlisted values ​​within the range of the composition.

[0107] In this article, the gram capacity of the positive electrode active material at a discharge rate of 0.33C can be measured by methods and equipment known in the art. An example is as follows: at 25°C, a fresh battery cell is charged to 3.8V at a constant current of 0.33C, then charged at a constant voltage of 3.8V to a cutoff current of 0.05C. After a pause of 5 minutes, the battery cell is discharged at a constant current of the corresponding rate (such as 0.33C), and the discharge cutoff voltage is 2V. The above steps are used to charge and discharge continuously for 3 times, and the capacity of the third time is used as the battery cell test capacity. Combined with the mass of the positive electrode active material, the gram capacity of the positive electrode active material at a discharge rate of 0.33C can be calculated.

[0108] The gram capacity of the positive electrode active material is within the above range, which is beneficial to improving the energy density of the battery.

[0109] In some embodiments, the lithium ion diffusion coefficient of the positive electrode active material is 3×10 -14 cm 2 / s-8×10 - 14 cm 2 / s.

[0110] In this article, the term "lithium ion diffusion coefficient" refers to the diffusion and mass transfer rate of lithium ions under a unit concentration gradient, and is an important indicator to characterize the speed of lithium ion diffusion.

[0111] In some embodiments, the lithium ion diffusion coefficient of the positive electrode active material may be 3×10 -14 cm 2 / s, 4×10 -14 cm 2 / s, 5×10 -14 cm 2 / s, 6×10 -14 cm 2 / s, 7×10 -14 cm 2 / s, 8×10 -14 cm 2 / s or the range composed of any two of the above lithium ion diffusion coefficients or other values ​​not listed within the range.

[0112] In this article, the lithium ion diffusion coefficient of the positive electrode active material can be measured by methods and equipment known in the art. For example, the battery cell capacity is adjusted to 50% SOC, and the discharge is continued at 1C rate for 30s, and the relaxation time is 2min. According to the formula The lithium ion diffusion coefficient at 50% SOC is calculated, which is the lithium ion diffusion coefficient of the positive electrode active material.

[0113] When the lithium ion diffusion coefficient of the positive electrode active material is within the above range, it is beneficial to further improve the rate performance of the battery.

[0114] In some embodiments, the lithium-containing phosphate includes a component having the following general formula:

[0115] Li m Fe x P y O j Q q ,

[0116] Among them, Q includes one or more of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.8≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0≤q≤0.1.

[0117] When used in this article, "lithium-containing phosphates include components having the following general formula" is not limited to substances represented by the molecular general formula, but also includes other substances formed after further appropriate modification on the basis of the molecular general formula, which is not limited here. The use of "general formula" is only for the convenience of description and is not intended to limit this application. It can be understood that new materials or new substances obtained by appropriate modification on the basis of the listed positive active materials are also within the scope of positive active materials. The aforementioned appropriate modification refers to acceptable modification methods for positive active materials, and non-limiting examples include coating modification.

[0118] In some embodiments, m can be 0.8, 0.85, 0.9, 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, or a range consisting of any two of the above m, or a value in a range consisting of.

[0119] In some embodiments, x can be 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, or a range consisting of any two of the foregoing x, or a value in a range consisting of the foregoing.

[0120] In some embodiments, y may be 0.95, 0.98, 1.0, or a range consisting of any two of the above y or a value in a range consisting of the above.

[0121] In some embodiments, j can be 3.5, 3.6, 3.7, 3.8, 3.9, 4, or a range consisting of any two of the above z, or a value in a range consisting of.

[0122] In some embodiments, q can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range consisting of any two of the above q, or a value in the range consisting of.

[0123] In some embodiments, the modifying element Q may exist in the lithium phosphate-containing material in the form of a doping element, and may also exist in the coating layer of the lithium phosphate-containing material in the form of a coating element.

[0124] In some embodiments, the molar ratio of lithium element to iron element in the positive electrode active material is 1.01-1.06.

[0125] In some embodiments, the molar ratio of the iron element to the phosphorus element in the positive electrode active material is 0.96-1.

[0126] In some embodiments, the molar ratio of the iron element to the phosphorus element in the positive electrode active material is 0.96-0.98.

[0127] Herein, the molar ratio of the iron element to the phosphorus element in the positive electrode active material can be measured by methods and equipment known in the art, for example, the test method of "the molar ratio of the lithium element to the iron element in the positive electrode active material" can be referred to above.

[0128] In some embodiments, the molar ratio of iron to phosphorus in the positive electrode active material may be 0.96, 0.97, 0.98, 0.99, 1, or a range consisting of any two of the above molar ratios, or other unlisted values ​​within the range.

[0129] The molar ratio of lithium to iron and the molar ratio of iron to phosphorus in the positive electrode active material are within the above ranges, which is conducive to further reducing the impurities in the positive electrode active material, further reducing the iron dissolution rate of the positive electrode active material, and further improving the gram capacity of the positive electrode active material and the cycle stability of the secondary battery. Furthermore, the appropriate molar ratio of lithium to iron and the molar ratio of iron to phosphorus are also conducive to further improving the lithium ion diffusion coefficient of the positive electrode active material.

[0130] [Method for preparing battery cell]

[0131] The present application also provides a method for preparing a battery cell, which comprises at least the following steps:

[0132] Preparation of positive electrode active material: mixing raw materials including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; treating the slurry to obtain a precursor material; sintering the precursor material to obtain a positive electrode active material, wherein the positive electrode active material includes a lithium-containing phosphate material, the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06, and the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L;

[0133] A battery cell is prepared using the positive electrode active material.

[0134] In some embodiments, the iron dissolution rate of the positive electrode active material can be 0 mg / L, 3 mg / L, 5 mg / L, 6 mg / L, 8 mg / L, 10 mg / L, or a range consisting of any two of the above iron dissolution rates or other unlisted values ​​within the range.

[0135] In some embodiments, the molar ratio of lithium to iron in the positive electrode active material may be 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, or any range of any two of the above molar ratios or other values ​​not listed within the range.

[0136] Compared with the solid phase method for preparing positive electrode active materials, the preparation method of the present application prepares the positive electrode active material by a one-step liquid phase co-precipitation method, which does not require a complicated precursor preparation process and high temperature and high pressure reaction conditions, thereby reducing the production cost of lithium iron phosphate materials.

[0137] The preparation method of the embodiment of the present application controls the molar ratio of lithium to iron in the positive electrode active material within the above-mentioned range, so that the positive electrode active material has excellent gram capacity, and is beneficial to the formation of pure phase lithium iron phosphate during the sintering process of preparing the positive electrode active material, thereby reducing the iron dissolution rate of the positive electrode active material; the iron, phosphorus and lithium elements in the positive electrode active material prepared by the liquid phase co-precipitation method adopted in the embodiment of the present application are uniformly distributed at the atomic level, which is beneficial to enhance the binding of phosphate to iron ions, thereby further reducing the iron dissolution rate of the positive electrode active material, so that the iron dissolution rate of the positive electrode active material meets the above-mentioned range, and the positive electrode active material has excellent cycle stability while taking into account good gram capacity.

[0138] In some embodiments, the first lithium source includes lithium sulfate.

[0139] Lithium sulfate has the advantages of abundant sources, low cost, good water solubility, etc., and is suitable for the preparation method of the embodiment of the present application, which is beneficial to reduce the cost of raw materials, thereby further reducing the production cost of lithium iron phosphate materials.

[0140] In some embodiments, the molar ratio of lithium in the first lithium source to iron in the iron source is greater than 1 and less than or equal to 1.06. Optionally, the molar ratio of lithium in the first lithium source to iron in the iron source is 1.01-1.06.

[0141] In some embodiments, the molar ratio of lithium in the first lithium source to iron in the iron source can be 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, or a range consisting of any two of the above molar ratios or other unlisted values ​​within the range.

[0142] In some embodiments, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-1.

[0143] In some embodiments, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-0.98.

[0144] In some embodiments, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source can be 0.96, 0.97, 0.98, 0.99, 1, or a range consisting of any two of the above molar ratios, or other unlisted values ​​within the range.

[0145] When the molar ratio of lithium in the first lithium source to iron in the iron source, and the molar ratio of iron in the iron source to phosphorus in the phosphorus source are within the above ranges, it is beneficial to form pure phase lithium iron phosphate during the sintering process, further reduce the iron dissolution rate of the prepared positive electrode active material, and further improve the gram capacity and cycle stability of the positive electrode active material. Furthermore, the appropriate molar ratio of lithium to iron, and the molar ratio of iron to phosphorus are also beneficial to further improve the lithium ion diffusion coefficient of the positive electrode active material.

[0146] In some embodiments, the preparation of the positive electrode active material includes at least the following steps: mixing a raw material including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; adding a pH adjuster to a pH value of the slurry greater than or equal to 7 to obtain a second slurry; separating the second slurry to obtain a precursor material; and sintering the precursor material to obtain the positive electrode active material.

[0147] In some embodiments, a pH adjuster is added to the slurry until the pH value is greater than or equal to 7 and less than or equal to 14.

[0148] In some embodiments, the pH adjuster is added to the slurry until the pH value is 7, 8, 9, 10, 11, 12, 13, 14, or a range consisting of any two of the above pH values, or other values ​​not listed within the range.

[0149] By adding a pH adjuster to adjust the pH of the slurry to be greater than or equal to 7, it is beneficial to further precipitate the lithium ions in the slurry, so that the molar ratio of lithium element to iron element in the precursor material is within a suitable range, for example, the molar ratio is 1.01-1.06, which is beneficial to the formation of a purer lithium iron phosphate during the sintering process, so that the iron dissolution rate of the prepared positive electrode active material is within a suitable range, further taking into account the excellent gram capacity and cycle stability.

[0150] In some embodiments, the pH adjuster includes one or more of ammonium carbonate and ammonium bicarbonate.

[0151] The above-mentioned types of pH adjusters are compatible with the preparation method of the present application.

[0152] In some embodiments, the preparation of the positive electrode active material further includes: separating the second slurry to obtain a solid material; adding a carbon source to the solid material and grinding it to obtain a precursor material; and sintering the precursor material to obtain the positive electrode active material.

[0153] The precursor material includes a carbon source. The surface of the positive electrode active material prepared by sintering is evenly coated with a highly conductive carbon layer, which is beneficial to improving the conductivity of the positive electrode active material. In addition, carbon can be used as a reducing agent to reduce Fe 3+ Reduction to Fe 2+ , which is conducive to further improving the gram capacity of the positive electrode active material.

[0154] In some embodiments, the mass content of the carbon source is 1%-5% based on the mass of the solid material.

[0155] In some embodiments, based on the mass of the solid material, the mass content of the carbon source can be 1%, 2%, 3%, 4%, 5% or a range consisting of the mass contents of any two of the above carbon sources or other unlisted values ​​within the range.

[0156] By controlling the amount of carbon source added within a suitable range, the thickness of the carbon coating layer on the surface of the prepared positive electrode active material is suitable, which is beneficial to further improve the conductivity and gram capacity of the positive electrode active material.

[0157] In some embodiments, the carbon source includes one or more of glucose, carbon powder, sucrose, and polyethylene glycol.

[0158] In some embodiments, the preparation method further includes: separating the second slurry to obtain a solid material; adding a carbon source and an additive to the solid material and grinding the solid material to obtain a precursor material; and sintering the precursor material to obtain a positive electrode active material.

[0159] In some embodiments, the additive includes one or more of zirconium oxide, titanium dioxide, aluminum oxide, and magnesium oxide.

[0160] The precursor material includes additives, so that the positive electrode active material obtained by sintering includes modifying elements, which is beneficial to further improve the cycle stability of the positive electrode active material.

[0161] In some embodiments, the mass content of the additive is 500 ppm-5000 ppm based on the mass of the solid material.

[0162] In some embodiments, based on the mass of the solid material, the mass content of the additive can be 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, or a range consisting of the mass contents of any two of the above additives or other unlisted values ​​within the range.

[0163] Controlling the amount of additives added within an appropriate range is beneficial to further improving the gram capacity and cycle stability of the positive electrode active material.

[0164] In some embodiments, the preparation of the positive electrode active material includes at least the following steps: mixing a raw material including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; adding a pH adjuster to a pH of the slurry greater than or equal to 7 to obtain a second slurry; separating the second slurry to obtain a solid material; adding a carbon source and an additive to the solid material, and grinding to obtain a precursor material; sintering the precursor material to obtain the positive electrode active material, wherein the first lithium source includes lithium sulfate, the positive electrode active material includes a lithium-containing phosphate material, the molar ratio of lithium element to iron element in the positive electrode active material is 1.01-1.06, and the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L.

[0165] The above preparation method uses cheap water-soluble lithium sulfate as a lithium source and prepares the positive electrode active material by a one-step liquid phase co-precipitation method, which reduces the cost of lithium iron phosphate materials and the iron dissolution rate of the positive electrode active material, and is conducive to the improvement of the cycle stability of the secondary battery. By adding a pH regulator to adjust the pH of the slurry to be greater than or equal to 7, it is conducive to further precipitating the lithium ions in the slurry, so that the molar ratio of lithium element to iron element in the precursor material is within a suitable range, which is conducive to forming a more pure phase lithium iron phosphate during the sintering process, so that the iron dissolution rate of the positive electrode active material is within a suitable range, and the positive electrode active material has excellent cycle stability while taking into account good gram capacity. Further, a carbon source and an additive are added to the solid material, and a precursor material is obtained after grinding, which is conducive to further improving the gram capacity and cycle stability of the positive electrode active material. In summary, the above preparation method shortens the preparation process of lithium iron phosphate and reduces its production cost, and the prepared positive electrode active material has a lower iron dissolution rate. The positive electrode active material of the embodiment of the present application has excellent cycle stability while taking into account good gram capacity.

[0166] In some embodiments, the preparation of the positive electrode active material includes at least the following steps: mixing a raw material including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; separating the slurry to obtain a first solid material; washing the first solid material, and sintering the first solid material after washing to obtain a second solid material; adding a second lithium source to the second solid material, and grinding to obtain a precursor material; sintering the precursor material to obtain the positive electrode active material.

[0167] The preparation method of the present application obtains the first solid material after washing, precipitation and separation, which can effectively remove the impurity ions such as sulfate introduced by the first lithium source in the first solid material, reduce the impurity content dissolved into the electrolyte, and then reduce the degree of side reactions, and further improve the cycle performance of the secondary battery. However, washing will dissolve the lithium element in the first solid material, resulting in a molar ratio of lithium element to iron element in the second solid material that is too small. If it is directly used for sintering to prepare positive electrode active materials, it will increase the iron dissolution rate of the positive electrode active material, for example, greater than 10 mg / L, and reduce its gram capacity; therefore, further, the preparation method of the present application adds a second lithium source to the second solid material, so that the molar ratio of lithium element to iron element in the precursor material used for sintering to prepare positive electrode active materials is within a suitable range, which is conducive to the formation of a more pure phase of lithium iron phosphate during the sintering process, so that the iron dissolution rate of the positive electrode active material is within a suitable range, and the prepared positive electrode active material has a more excellent cycle stability and excellent gram capacity. In summary, the above preparation method reduces the production cost of lithium iron phosphate. At the same time, the obtained positive electrode active material has a lower iron dissolution rate and a further reduced impurity ion content, which is beneficial to further improve the cycle stability of the positive electrode active material of the present application while taking into account the gram capacity.

[0168] In some embodiments, based on the total mass of the positive electrode active material, the mass content of sulfur in the positive electrode active material is 0 ppm-50 ppm.

[0169] When lithium sulfate is used as the first lithium source, the first solid material obtained after washing, precipitation and separation can effectively remove sulfate ions in the first solid, so that the mass content of sulfur element in the positive electrode active material is within the above range, which is beneficial to further improve the cycle performance of the positive electrode active material of the present application.

[0170] In some embodiments, the first solid material is washed 3-5 times.

[0171] In some embodiments, the first solid material may be washed 3, 4, 5 times or a range consisting of any two of the above washing times.

[0172] Controlling the number of washing times within the above range is beneficial to dissolving as little lithium as possible in the first solid material while removing impurities to the greatest extent, which is beneficial to further reduce the cost of subsequent lithium replenishment and take into account the gram capacity and cycle stability of the secondary battery.

[0173] In some embodiments, the second lithium source includes one or more of lithium carbonate and lithium hydroxide.

[0174] In some embodiments, the temperature of sintering the first solid material is 300°C-400°C.

[0175] In some embodiments, the time for sintering the first solid material is 3 hours to 5 hours.

[0176] In some embodiments, the temperature for sintering the first solid material can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, or a range composed of any two of the above temperatures or other unlisted values ​​within the range.

[0177] In some embodiments, the time for sintering the first solid material can be 3 h, 4 h, 5 h, or a range of any two of the above time periods, or other unlisted values ​​within the range.

[0178] Controlling the temperature and time of sintering the first solid material within the above range is conducive to removing moisture from the first solid material and converting it into a second solid material including an iron phosphate phase. By testing the iron-lithium ratio of the second solid material, it is convenient to calculate the amount of the second lithium source that needs to be added. The above sintering temperature and time are conducive to uniformly mixing the sintered second solid material and the second lithium source to obtain a precursor material, thereby improving the efficiency of subsequent sintering of the precursor material.

[0179] In some embodiments, the preparation of the positive electrode active material further comprises: adding a second lithium source and a carbon source to the second solid material, and grinding to obtain a precursor material; and sintering the precursor material to obtain the positive electrode active material.

[0180] The precursor material includes a carbon source. The surface of the positive electrode active material prepared by sintering is evenly coated with a highly conductive carbon layer, which is beneficial to improving the conductivity of the positive electrode active material. In addition, carbon can be used as a reducing agent to reduce Fe 3+ Reduction to Fe 2+ , which is conducive to further improving the gram capacity of the positive electrode active material.

[0181] In some embodiments, the mass content of the carbon source is 1%-5% based on the mass of the second solid material.

[0182] In some embodiments, based on the mass of the second solid material, the mass content of the carbon source can be 1%, 2%, 3%, 4%, 5% or a range consisting of the mass contents of any two of the above carbon sources or other unlisted values ​​within the range.

[0183] By controlling the amount of carbon source added within a suitable range, the thickness of the carbon coating layer on the surface of the prepared positive electrode active material is suitable, which is beneficial to further improve the conductivity and gram capacity of the positive electrode active material.

[0184] In some embodiments, the carbon source includes one or more of glucose, carbon powder, sucrose, and polyethylene glycol.

[0185] In some embodiments, the preparation method further comprises: adding a second lithium source, a carbon source, and an additive to the second solid material, and grinding to obtain a precursor material; and sintering the precursor material to obtain a positive electrode active material.

[0186] In some embodiments, the additive includes one or more of zirconium oxide, titanium dioxide, aluminum oxide, and magnesium oxide.

[0187] The precursor material includes additives, so that the positive electrode active material obtained by sintering includes modifying elements, which is beneficial to further improve the cycle stability of the positive electrode active material.

[0188] In some embodiments, the mass content of the additive is 500 ppm-5000 ppm based on the mass of the second solid material.

[0189] In some embodiments, based on the mass of the second solid material, the mass content of the additive can be 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, or a range consisting of the mass contents of any two of the above additives or other unlisted values ​​within the range.

[0190] Controlling the amount of additives added within an appropriate range is beneficial to further improving the gram capacity and cycle stability of the positive electrode active material.

[0191] In some embodiments, the preparation of the positive electrode active material includes at least the following steps: mixing a raw material including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; separating the slurry to obtain a first solid material; washing the first solid material, and sintering the first solid material after washing to obtain a second solid material; adding a second lithium source, a carbon source, and an additive to the second solid material, and grinding to obtain a precursor material; sintering the precursor material to obtain the positive electrode active material; wherein the first lithium source includes lithium sulfate, the positive electrode active material includes a lithium-containing phosphate material, the molar ratio of lithium element to iron element in the positive electrode active material is 1.01-1.06, the iron dissolution rate of the positive electrode active material is 0mg / L-10mg / L, and based on the total mass of the positive electrode active material, the mass content of sulfur element in the positive electrode active material is 0ppm-50ppm.

[0192] The above preparation method uses cheap water-soluble lithium sulfate as a lithium source and prepares the positive electrode active material by a one-step liquid phase co-precipitation method, which reduces the cost of lithium iron phosphate materials and the iron dissolution rate of the positive electrode active material, and is beneficial to the improvement of the cycle stability of the secondary battery. Furthermore, the first solid material obtained after washing, precipitation and separation can effectively remove impurity ions such as sulfate introduced by the cheap lithium sulfate raw material in the first solid material, further improving the cycle stability of the secondary battery. By adding a second lithium source, a carbon source, and an additive to the second solid material, the molar ratio of lithium element to iron element in the precursor material used for sintering to prepare the positive electrode active material is within a suitable range, and the positive electrode active material prepared by sintering includes a modifying element, and the surface of the positive electrode active material is uniformly coated with a highly conductive carbon layer, thereby further making the iron dissolution rate of the positive electrode active material within a suitable range, and the prepared positive electrode active material has a more excellent cycle stability, while taking into account the excellent gram capacity. In summary, the above preparation method uses a cheap lithium source and reduces the production cost of lithium iron phosphate. At the same time, the obtained positive electrode active material has a lower iron dissolution rate and a further reduced sulfur content, which is beneficial to further improve the cycle stability of the positive electrode active material of the present application while taking into account the gram capacity.

[0193] In some embodiments, the temperature of sintering the precursor material is 650°C-750°C.

[0194] In some embodiments, the time for sintering the precursor material is 5 hours to 15 hours.

[0195] In some embodiments, the temperature of sintering the precursor material can be 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, or a range composed of any two of the above temperatures or other unlisted values ​​within the range.

[0196] In some embodiments, the sintering time of the precursor material can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, or a range composed of any two of the above time periods or other unlisted values ​​within the range.

[0197] Controlling the temperature and time of sintering the precursor within the above range is beneficial to improving the conversion rate of the precursor material into the lithium iron phosphate phase, further reducing the iron dissolution rate of the positive electrode active material and improving the gram capacity of the positive electrode active material; further, the above sintering temperature and time are beneficial to the reaction of the added carbon source and trivalent iron ions into divalent iron ions, and the surface of the sintered positive electrode active material has a uniform carbon coating layer, thereby further improving the gram capacity and cycle stability of the positive electrode active material.

[0198] In some embodiments, the iron source includes one or more of ferrous sulfate and ferric sulfate.

[0199] In some embodiments, the phosphorus source includes one or more of diammonium phosphate, phosphoric acid, and diammonium phosphate.

[0200] [Positive electrode]

[0201] The present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer comprising a positive electrode active material, a binder and a conductive agent, the positive electrode active material comprising the positive electrode active material of any embodiment of the present application or the positive electrode active material prepared by the preparation method of any embodiment of the present application.

[0202] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0203] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0204] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0205] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0206] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0207] [Negative electrode]

[0208] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0209] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0210] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0211] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0212] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0213] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0214] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0215] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0216] [Electrolytes]

[0217] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application embodiment has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, solid or gel.

[0218] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0219] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0220] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0221] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0222] [Isolation film]

[0223] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0224] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0225] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0226] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0227] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0228] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.

[0229] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0230] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0231] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0232] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0233] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0234] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0235] In addition, the present application also provides a battery device, including the battery cell provided in the first aspect of the present application, and the battery device includes at least one of a battery module, a battery pack, and an energy storage battery.

[0236] In addition, the present application also provides an electric device, which includes the battery cell provided in the first aspect of the present application. The battery cell, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0237] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0238] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.

[0239] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0240] Example

[0241] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0242] Preparation method

[0243] Example 1

[0244] 1) Preparation of positive electrode active materials

[0245] (1) 1 mol / L FeSO4 solution and 1 mol / L Li2SO4 solution were added to a stirred tank and mixed evenly, the reactor was filled with nitrogen for protection, the molar ratio of Li / Fe was controlled to be 1.03, and then ammonium dihydrogen phosphate was added to control the molar ratio of Fe / P to be 0.97, and the mixture was sand-milled and stirred for 30 minutes to obtain a slurry;

[0246] (2) adding ammonium carbonate until the pH of the slurry is greater than or equal to 7, and after precipitation is complete, obtaining a second slurry;

[0247] (3) centrifugally filtering the second slurry to obtain a solid material, adding a mixture of glucose and polyethylene glycol accounting for 4 wt % of the solid material to the solid material, wherein the mass ratio of glucose to polyethylene glycol is 1:1, sand-milling with water as a medium to uniformly disperse the solid material, and spray drying to obtain a precursor material;

[0248] (4) The precursor material was placed in a sagger and sintered at 700°C for 10 hours, with nitrogen gas introduced for protection during the sintering process. The sintered material was rolled, air flow crushed, and sieved to finally obtain a lithium iron phosphate positive electrode active material, with a Dv90 of 2.78 μm and a Dv99 of 5.61 μm.

[0249] 2) Preparation of positive electrode

[0250] The prepared lithium iron phosphate positive electrode active material, conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97:1:2, and then a solvent N-methylpyrrolidone was added, and the mixture was fully stirred and mixed to prepare a positive electrode slurry;

[0251] The positive electrode slurry was prepared at 20 mg / cm 2 The single-sided weight is coated on the single side of the positive electrode current collector aluminum foil, and then dried, cold pressed and cut to obtain the positive electrode sheet.

[0252] 3) Preparation of negative electrode sheet

[0253] Artificial graphite, conductive carbon black, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and solvent water are uniformly mixed in a weight ratio of 97:1:1:1:100 to obtain a negative electrode slurry;

[0254] The negative electrode slurry was prepared at 10 mg / cm 2 The single-sided weight is coated on both sides of the negative electrode collector copper foil, and after drying, cold pressing and slitting, the negative electrode sheet is obtained.

[0255] 4) Preparation of electrolyte

[0256] At 25° C., ethylene carbonate, diethyl carbonate, and dimethyl carbonate were mixed in a volume ratio of 1:1:1, and LiPF6 was dissolved in the above solution to obtain an electrolyte solution. In the electrolyte solution, the concentration of LiPF6 was 1 mol / L.

[0257] 5) Isolation film

[0258] A polyethylene film with a thickness of 10 μm was used as the separator.

[0259] 6) Preparation of secondary batteries

[0260] The positive electrode sheet, separator and negative electrode sheet are stacked in order to obtain a laminated battery cell; the battery cell is placed in an outer package, and the prepared electrolyte is added. After packaging, standing, forming, aging and other processes, the secondary battery of Example 1 is obtained.

[0261] The preparation method of the secondary battery of Example 2 is basically similar to that of Example 1, except for the preparation of the positive electrode active material, specifically the different molar ratio of Li / Fe in step (1).

[0262] The preparation method of the secondary battery of Example 3-4 is basically similar to that of Example 1, except for the preparation of the positive electrode active material, specifically the molar ratio of Fe / P in step (1).

[0263] The preparation method of the secondary battery of Example 5 is basically similar to that of Example 1, except for the preparation of the positive electrode active material. The preparation method of the positive electrode active material is as follows:

[0264] (1) 1 mol / L FeSO4 solution and 1 mol / L Li2SO4 solution were added to a stirred tank and mixed evenly. The reactor was filled with nitrogen for protection, and the molar ratio of Li / Fe was controlled to be 1.03. Subsequently, ammonium dihydrogen phosphate was added to control the molar ratio of Fe / P to be 0.97. After stirring and reacting for 30 minutes, precipitation was complete to obtain a slurry;

[0265] (2) filtering the slurry to obtain a first solid material, washing the first solid material with pure water for 3 times, drying after washing, and sintering at 350° C. for 5 h in a nitrogen atmosphere to obtain a second solid material;

[0266] (3) adding lithium carbonate to the second solid material, the mass of the added lithium carbonate is such that the molar ratio of lithium element to iron element in the positive electrode active material is controlled to be 1.03, adding a mixture of glucose and polyethylene glycol, the mass ratio of glucose and polyethylene glycol is 1:1, and the added amount is 4wt% of the mass of the second solid material, using water as a medium for sand grinding and uniform dispersion, and spray drying to obtain a precursor material;

[0267] (4) The precursor material was placed in a sagger and sintered at 700°C for 10 hours, with nitrogen gas introduced for protection during the sintering process. The sintered material was rolled, air flow crushed, and sieved to finally obtain a lithium iron phosphate positive electrode active material, with a Dv90 of 3.76 μm and a Dv99 of 7.01 μm.

[0268] The preparation method of the secondary battery of Examples 6-7 is basically similar to that of Example 5, except for the preparation of the positive electrode active material, specifically the different molar ratio of Li / Fe in step (3).

[0269] The preparation method of the secondary battery of Comparative Example 1 is basically similar to that of Example 1, except for the preparation of the positive electrode active material. The preparation method of the positive electrode active material of Comparative Example 1 is:

[0270] (1) Add 1 mol / L FeSO4 solution and 1 mol / L H3PO4 solution into a stirring kettle and mix them evenly. Add hydrogen peroxide and sodium hydroxide to adjust the pH to neutral and control the Fe / P molar ratio to 1. After precipitation is complete, centrifuge and filter. Wash the solid with clean water for 3 times, dry it, and sinter it at 300°C for later use.

[0271] (2) The solid in step (1) is sand-milled and mixed with lithium carbonate to uniformly obtain a Li / Fe ratio of 1.03, 4 wt % of a mixture of glucose and polyethylene glycol is added, water is used as a medium to sand-mill and disperse the mixture uniformly, and then spray-dried to obtain a powder material.

[0272] (3) The powder material in step (2) is placed in a sagger and sintered at 700° C. for 10 h, with nitrogen gas introduced during the sintering process for protection. The sintered material is crushed and sieved to obtain the target lithium iron phosphate positive electrode material.

[0273] The preparation method of the secondary battery of Comparative Example 2 is basically similar to that of Example 1, except for the preparation of the positive electrode active material. Specifically, the preparation process of the positive electrode active material of Comparative Example 2 does not include the step (2) of adding ammonium carbonate until the pH of the slurry is greater than or equal to 7, and waiting for the precipitation to be complete to obtain the second slurry. After the step (1) is completed, the operation of step (3) is directly performed.

[0274] The preparation method of the secondary battery of Comparative Example 3 is basically similar to that of Example 5, except for the preparation of the positive electrode active material. Specifically, the preparation process of the positive electrode active material of Comparative Example 3 does not include the operation of supplementing the second lithium source lithium carbonate in step (3), and in step (3), a mixture of glucose and ethylene glycol is directly added to the second solid material for subsequent operations.

[0275] 2. Performance Test

[0276] (1) Test on the dissolution rate of iron in positive electrode active materials

[0277] Disassemble the battery and take out the positive electrode sheet, peel off the active material film layer of the positive electrode sheet, dissolve and filter with N-methylpyrrolidone (NMP) solvent, wash thoroughly with NMP to remove the binder; dry to obtain powder for subsequent characterization tests. Weigh 5g of powder, add 100mL of 0.008mol / L hydrochloric acid, stir at 25°C for 30min, then stand in a 25°C water bath for 2h, filter to obtain the filtrate, and test the concentration of iron ions in the filtrate. The iron ion concentration in the filtrate was tested by inductive plasma emission spectroscopy (ICP), and the test method refers to the national standard EPA 6010D-2018 and JY / T 0567-2020.

[0278] (2) Test of the mass content of each element in the positive electrode active material

[0279] Disassemble the battery and take out the positive electrode sheet, peel off the active material film layer of the positive electrode sheet, dissolve and filter with NMP solvent, wash with NMP to remove the binder, and dry to obtain powder for subsequent characterization tests. Weigh 0.5g of powder, add 10mL of aqua regia and microwave digest for 20min, then measure 1mL of sample and dilute to 100mL for standby use. The sulfur content in the above samples was tested according to the national standard EPA 6010D-2018JY / T 0567-2020 inductively coupled plasma emission spectrometry, and finally the mass content of sulfur in the positive active material was calculated.

[0280] According to the national standard EPA 6010D-2018JY / T 0567-2020 inductively coupled plasma emission spectrometry, the contents of Li, Fe and P in the above samples were tested, and the molar ratio of Li / Fe and the molar ratio of Fe / P in the positive electrode active material were calculated.

[0281] (3) Dv90 and Dv99 tests of positive electrode active materials

[0282] The volume distribution particle sizes Dv90 and Dv99 of the positive electrode active material can be measured by a laser particle size analyzer according to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.

[0283] (4) Gram capacity test at 0.33C discharge rate

[0284] At 25°C, the fresh battery cell is charged to 3.8V at a constant current of 0.33C, then charged at 3.8V to a cut-off current of 0.05C, and then discharged at a constant current of 0.33C after a 5-minute pause, with a discharge cut-off voltage of 2V. The above steps are used to charge and discharge continuously for 3 times, and the capacity of the third time is used as the battery cell test energy. Combined with the mass of the positive electrode active material, the gram capacity of the positive electrode active material at a discharge rate of 0.33C can be calculated.

[0285] (5) Lithium ion diffusion coefficient test

[0286] Adjust the cell capacity to 50% SOC, discharge at 1C rate for 30s, and relax for 2min. According to the formula The diffusion coefficient of lithium ions at 50% SOC was calculated.

[0287] (6) Capacity retention rate test

[0288] The test steps are as follows: at 25°C, charge to 3.8V at 1C constant current, then charge to 0.05C at 3.8V constant voltage, leave for 5 minutes, then discharge to 2.0V at 1C, record the discharge capacity as initial capacity C0, repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle, then the battery capacity retention rate after each cycle Pn = (Cn / C0) × 100%. The battery capacity retention rate after 500 cycles can be used to reflect the difference in cycle performance.

[0289] III. Analysis of test results of various embodiments and comparative examples

[0290] Secondary batteries of various embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1 and 2 below.

[0291] Table 1

[0292]

[0293] Table 2

[0294]

[0295] As can be seen from Tables 1 and 2, Examples 1-7 provide a battery cell, the battery cell comprising a positive electrode plate, a negative electrode plate and an electrolyte, the positive electrode plate comprising a positive electrode collector and a positive electrode film layer disposed on at least one side of the positive electrode collector, the positive electrode film layer comprising a positive electrode active material, the positive electrode active material comprising a lithium-containing phosphate material, the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L, and the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06.

[0296] From the comparison between Examples 1-7 and Comparative Examples 1-3, it can be seen that the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L, and the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06. The positive electrode active material of the embodiment of the present application has excellent cycle stability and also has good gram capacity.

[0297] By comparing Examples 1-3 and 5-7 with Example 4, it can be seen that the iron dissolution rate of the positive electrode active material is 0 mg / L-5 mg / L, and the cycle stability of the battery is further improved.

[0298] From the comparison between Examples 5-7 and Examples 1-4, it can be seen that the mass content of sulfur in the positive electrode active material is 0 ppm-50 ppm, and the cycle stability of the battery is further improved.

[0299] It can be seen from Examples 1-7 and Comparative Example 1 that the Dv90 of the positive electrode active material is 2 μm-5 μm and / or the Dv99 is 4 μm-8 μm, and the lithium ion diffusion coefficient of the positive electrode active material is improved.

[0300] From the comparison between Examples 1-7 and Comparative Examples 2-3, it can be seen that when the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06 and / or the molar ratio of iron element to phosphorus element in the positive electrode active material is 0.96-1, the iron dissolution rate of the positive electrode active material is further reduced and the gram capacity is further improved.

[0301] From the comparison between Examples 1-3 and Example 4, it can be seen that when the molar ratio of the iron element to the phosphorus element in the positive electrode active material is 0.96-0.98, the cycle stability of the battery is further improved.

[0302] The preparation method of the positive electrode active material of Examples 1-7 includes the following steps: mixing a raw material including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; treating the slurry to obtain a precursor material; sintering the precursor material to obtain the positive electrode active material, wherein the molar ratio of the lithium element to the iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06, and the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L.

[0303] From the comparison between Examples 1-7 and Comparative Example 1, it can be seen that compared with Comparative Example 1, which uses a solid phase method to prepare the positive electrode active material, the preparation method of Examples 1-7 shortens the process and uses lithium sulfate as a lithium source, which is beneficial to reducing the preparation cost of the positive electrode active material. Furthermore, the liquid phase co-precipitation method of Examples 1-7 is beneficial to reducing the iron dissolution rate of the positive electrode active material, reducing the Dv90 and Dv99 of the positive electrode active material, and improving the lithium ion diffusion coefficient of the positive electrode active material, and the cycle stability of the battery is improved.

[0304] From the comparison between Examples 1-7 and Comparative Examples 2-3, it can be seen that the preparation method of Examples 1-7 makes the molar ratio of lithium element to iron element in the positive electrode active material greater than 1 and less than or equal to 1.06, the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L, and the battery has excellent cycle stability, which is beneficial to further improve the gram capacity of the positive electrode active material.

[0305] From the comparison between Examples 1-4 and Comparative Example 2, it can be seen that the preparation method of Examples 1-4 adds a pH regulator to the slurry pH greater than or equal to 7 through step (2), which is beneficial to make the molar ratio of lithium element to iron element in the positive electrode active material within a suitable range, for example, greater than 1 and less than or equal to 1.06, thereby further reducing the iron ion dissolution rate of the positive electrode active material, while taking into account the gram capacity while having good cycle stability of the battery.

[0306] From the comparison between Examples 5-7 and Comparative Example 3, it can be seen that the preparation method of Examples 5-7 supplements the second lithium source through step (3), which is beneficial to make the molar ratio of lithium element to iron element in the positive electrode active material within a suitable range, for example, greater than 1 and less than or equal to 1.06, thereby further reducing the dissolution rate of iron ions in the positive electrode active material, while taking into account the gram capacity while having good cyclic stability of the battery.

[0307] From the comparison between Examples 1-4 and Examples 5-7, it can be seen that the preparation method of Examples 5-7 uses the preparation process of removing sulfur impurities by washing and supplementing the second lithium source, so that based on the total mass of the positive electrode active material, the mass content of sulfur element in the positive electrode active material is 0ppm-50ppm, and the cycle stability of the battery is further improved.

[0308] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A battery cell, characterized in that: The battery cell includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a lithium-containing phosphate material, the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L, and the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.

06.

2. The battery cell according to claim 1, characterized in that: The iron dissolution rate of the positive electrode active material is 0 mg / L-5 mg / L.

3. The battery cell according to claim 1 or 2, characterized in that: The mass content of sulfur in the positive electrode active material is 0 ppm-50 ppm based on the total mass of the positive electrode active material.

4. The battery cell according to any one of claims 1 to 3, characterized in that: The Dv90 of the positive electrode active material is 2 μm-5 μm.

5. The battery cell according to any one of claims 1 to 4, characterized in that: The Dv99 of the positive electrode active material is 4 μm-8 μm.

6. The battery cell according to any one of claims 1 to 5, characterized in that: The gram capacity of the positive electrode active material at a discharge rate of 0.33C is 145 mAh / g-152 mAh / g.

7. The battery cell according to any one of claims 1 to 6, characterized in that: The lithium ion diffusion coefficient of the positive electrode active material is 3×10 -14 cm 2 / s-8×10 -14 cm 2 / s.

8. The battery cell according to any one of claims 1 to 7, characterized in that: The lithium-containing phosphate includes a component having the following general formula: The m Fe x P y O j Q q , Among them, Q includes one or more of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, 0.8≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0≤q≤0.

1.

9. The battery cell according to any one of claims 1 to 8, characterized in that: The molar ratio of lithium to iron in the positive electrode active material is 1.01-1.06; and / or The molar ratio of the iron element to the phosphorus element in the positive electrode active material is 0.96-1, and optionally, 0.96-0.

98.

10. A method for preparing a battery monomer, characterized in that: The preparation method comprises at least the following steps: Preparation of positive electrode active materials: Mixing raw materials including a first lithium source, an iron source, and a phosphorus source with a solvent to obtain a slurry; treating the slurry to obtain a precursor material; sintering the precursor material to obtain the positive electrode active material, The positive electrode active material comprises a lithium-containing phosphate material, the molar ratio of lithium element to iron element in the positive electrode active material is greater than 1 and less than or equal to 1.06, and the iron dissolution rate of the positive electrode active material is 0 mg / L-10 mg / L; The battery cell is prepared using the positive electrode active material.

11. The preparation method according to claim 10, characterized in that: The first lithium source includes lithium sulfate.

12. The preparation method according to claim 10 or 11, characterized in that: The molar ratio of the lithium element in the first lithium source to the iron element in the iron source is greater than 1 and less than or equal to 1.

06. Optionally, the molar ratio of the lithium element in the first lithium source to the iron element in the iron source is 1.01-1.

06.

13. The preparation method according to any one of claims 10 to 12, characterized in that: The molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-1. Optionally, the molar ratio of the iron element in the iron source to the phosphorus element in the phosphorus source is 0.96-0.

98.

14. The preparation method according to any one of claims 10 to 13, characterized in that: The preparation of the positive electrode active material comprises at least the following steps: Mixing the raw materials including the first lithium source, the iron source, and the phosphorus source with the solvent to obtain the slurry; Adding a pH adjuster until the pH of the slurry is greater than or equal to 7 to obtain a second slurry; separating the second slurry to obtain the precursor material; The precursor material is sintered to obtain the positive electrode active material.

15. The preparation method according to claim 14, characterized in that: The pH adjuster includes one or more of ammonium carbonate and ammonium bicarbonate.

16. The preparation method according to claim 14 or 15, characterized in that: The preparation of the positive electrode active material also includes: separating the second slurry to obtain a solid material; Adding a carbon source to the solid material and grinding it to obtain the precursor material; The precursor material is sintered to obtain the positive electrode active material.

17. The preparation method according to claim 16, characterized in that: Based on the mass of the solid material, the mass content of the carbon source is 1%-5%.

18. The preparation method according to any one of claims 10 to 13, characterized in that: The preparation of the positive electrode active material comprises at least the following steps: Mixing the raw materials including the first lithium source, the iron source, and the phosphorus source with the solvent to obtain the slurry; separating the slurry to obtain a first solid material; washing the first solid material, and sintering the first solid material after washing to obtain a second solid material; Adding a second lithium source to the second solid material and grinding to obtain the precursor material; The precursor material is sintered to obtain the positive electrode active material.

19. The preparation method according to claim 18, characterized in that: The mass content of sulfur in the positive electrode active material is 0 ppm-50 ppm based on the total mass of the positive electrode active material.

20. The preparation method according to claim 18 or 19, characterized in that: The first solid material is washed 3-5 times.

21. The preparation method according to any one of claims 18 to 20, characterized in that: The second lithium source includes one or more of lithium carbonate and lithium hydroxide.

22. The preparation method according to any one of claims 18 to 21, characterized in that: The temperature of sintering the first solid material is 300° C.-400° C.; and / or The time for sintering the first solid material is 3h-5h.

23. The preparation method according to any one of claims 18 to 22, characterized in that: The preparation of the positive electrode active material also includes: Adding the second lithium source and the carbon source to the second solid material, and grinding to obtain the precursor material; The precursor material is sintered to obtain a positive electrode active material.

24. The preparation method according to claim 23, characterized in that: Based on the mass of the second solid material, the mass content of the carbon source is 1%-5%.

25. The preparation method according to any one of claims 10 to 24, characterized in that: The temperature for sintering the precursor material is 650° C.-750° C.; and / or The time for sintering the precursor material is 5h-15h.

26. The preparation method according to any one of claims 10 to 25, characterized in that: The iron source includes one or more of ferrous sulfate and ferric sulfate; and / or The phosphorus source includes one or more of diammonium phosphate, phosphoric acid, and diammonium hydrogen phosphate.

27. An electrical device, characterized in that: The invention comprises a battery cell according to any one of claims 1 to 9 or a battery cell obtained by the preparation method according to any one of claims 10 to 26.

Citation Information

Patent Citations

  • Lithium iron phosphate composite material with long cycle life, and positive electrode material, and preparation methods thereof

    CN112993227A

  • Positive electrode active material and preparation method thereof, positive electrode plate, secondary battery, battery module, battery pack and electric device

    CN116547835A

  • Preparation method of lithium iron phosphate, positive active material, positive pole piece, battery and electric device

    CN117088352A

  • Lithium manganese iron phosphate positive electrode material and preparation method thereof, battery and electric equipment

    CN118712378A

  • Cosmetic Container with Refill Structure

    KR102627782B1

Cited By

  • Lithium ion secondary battery, battery device, and power device

    CN120033312A